Soil health investment and Kansas commercial crop farm financial performance - Joseph, Delide (My University, 2025)
Context: Soil health investments are widely promoted for their environmental benefits, but their financial impacts, particularly on farm profitability, remain underexplored and vary widely across studies. Understanding these financial outcomes is crucial for informing farmer decision-making and shaping conservation policy. Objectives: This study aims to evaluate the relationship between soil health investments, defined as the combined adoption of multiple regenerative or conservation practices, and farm financial performance. It also investigates whether different quantification methods for soil health investments produce consistent farm-level classifications. Methods: The study uses farm-level data from the Kansas Farm Management Association and a farmer survey on soil health practices. Soil health investments are quantified using three classification methods: agronomic scoring, cluster-based classification, and threshold-based grouping. Financial performance is assessed through (1) a cluster analysis ranking farms based on net farm income ratio, return on assets, profit margin ratio, and (2) net farm income ratio. Ordered logistic regression is applied to determine the likelihood of farms achieving higher financial rankings, while OLS is used for net farm income ratio. The relationship between soil health investment and factors that determine profitability, specifically yield and expenses, are also estimated. To determine degree to which soil health investment relative to other observable factors predicts farm profitability, we also employ a random forest machine learning analysis. Results and conclusion: The three classifications used in this study produce different soil health investment rankings across farms with 10% consistently classified as high, 4% as medium, and 17% as low across all three methods. This variation highlights a key methodological insight: different classification approaches do not always agree, which has implications for how soil health investment is interpreted and linked to financial outcomes. Only higher agronomic soil health scores are consistently associated with stronger financial performance; lower expenses likely play a role in this relationship. Soil health investments have a weaker predictive power for farm profitability than farm size, structure, operator age, and weather, but can more easily be controlled by farm operators. Significance: This study underscores the need for standardized soil health measurement to validate survey or practice-based measures. Large, detailed field-level dataset on soil characteristics, practices, input use, and yields would assist in the creation of such measurements.
Keywords: Soil health investment; Farm financial performance; Soil health practices; Kansas commercial crop farms